2012
DOI: 10.2478/v10078-012-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effects of Soccer Small-Sided Games

Abstract: Over the last years there has been a substantial growth in research related to specific training methods in soccer with a strong emphasis on the effects of small-sided games. The increase of research in this topic is coincident with the increase of popularity obtained by specific soccer conditioning, which involves training players to deal with soccer match situations. Given the limited time available for fitness training in soccer, the effectiveness of small-sided games as a conditioning stimulus needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
220
1
47

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(276 citation statements)
references
References 46 publications
(119 reference statements)
8
220
1
47
Order By: Relevance
“…It has been shown to attain high commitment, positive behavior and training adherence for instance. 9 To the best of our knowledge no studies examined the effects of the verbal coach encouragement on mood state. Indeed, the verbal coach encouragement would directly impact the physical intensity (such as rating of perceived exertion (RPE)) of players' activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to attain high commitment, positive behavior and training adherence for instance. 9 To the best of our knowledge no studies examined the effects of the verbal coach encouragement on mood state. Indeed, the verbal coach encouragement would directly impact the physical intensity (such as rating of perceived exertion (RPE)) of players' activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to attain high commitment, positive behavior and training adherence for instance, during high-intensity training. 9 However, Rampinini et al 4 studied the effect of coaches' verbal encouragement in soccer players' on physiological responses during different modality of SSG: 3 vs. 3, 4 vs. 4, 5 vs. 5 and 6 vs. 6 players on small, medium and large pitches area. Researchers indicated that the heart rate (HR), blood lactate concentration (La) and RPE responses to SSG were significantly higher SSG with verbal coach encouragement in comparison with no-verbal coach encouragement during all SSG formats.…”
Section: Introductionmentioning
confidence: 99%
“…O futebol é um jogo esportivo coletivo caracterizado pela interdependência dinâmica de componentes técnicos, táticos e físicos em um contexto tático-situacional [1][2][3] . De forma a permitir maior especificidade das sessões de treinamento, recentemente propõem-se pequenos jogos como meios para aprimoramento de capacidades técnicas, físicas e psicológicas 4 em um contexto imprevisível, aleatório e complexo 1 caraterístico desta modalidade.…”
Section: Introductionunclassified
“…Un claro ejemplo de ello son las tareas en espacios reducidos, también conocidas como juegos reducidos (JR). En este tipo de tareas con balón se presentan actividades de entrenamiento que incluyen aspectos tácticos, técnicos y físicos, creando situaciones específicas y similares al juego real (Aguiar, Botelho, Lago, Maças, & Sampaio, 2012). La manipulación de las distintas variables de estos juegos reducidos, como por ejemplo número de jugadores, espacio por jugador, la consecución de diferentes objetivos, los ratios de trabajo-descanso, o las propias reglas de provocación que se puedan establecer, repercutirá directamente en las exigencias técnicas, tácticas o físicas de las tareas diseñadas (Clemente, Couceiro, Martins, & Mendes, 2013).…”
Section: Introductionunclassified